Waiting Period, Price Affordability, and Service Quality as The Determinants of Patient Satisfaction and Revisit Intention at Jala Ammari Navy Hospital, Makassar City - Angeline, Agiona; Herawati, Resy Eka; Putri, Eka Ananda (Green Publisher Indonesia, 2025)
Patient satisfaction has an impact on patient loyalty, especially on the intention to revisit and use the services offered by a hospital. The primary objective of this study is to analyze the impact of waiting period, price affordability, and service quality on patient satisfaction and revisit intention at Jala Ammari Navy Hospital in Makassar City. This study used a nonprobability sampling method with a consecutive sampling approach to select respondents, as it allowed researchers to collect data through questionnaires distributed to patients who visited the hospital on 1st - 30th April 2025. The data obtained were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The analysis revealed a clear hierarchy of importance among the examined factors, with service quality emerging as the most influential determinant (=0.423, p0.001). Regarding operational factors, waiting period showed a meaningful though relatively modest impact on satisfaction. The study's comprehensive measurement approach provided robust validation of the hypothesized relationships (Hair et al., 2022). The findings offer valuable evidence-based insights for hospital administrators seeking to improve patient care and foster long-term relationships with their patients within the context of a private hospital setting.